KOMUNITAS SUKU ASLI (STUDI KAPITAL SOSIOLOGI MASYARAKAT SUKU AKIT PESISIR DI DESA BERANCAH KECAMATAN BANTAN KABUPATEN BENGKALIS) - Rosaliza, MIta (Jurnal Ilmu Budaya, 2017)
The condition of coastal communities in various regions is generally characterized by the existence of several characteristics, such as poverty, socio-cultural backwardness and low human resources (HR). In this study the coastal community studied is Akit community social capital in Berancah village with high poverty level. This research aims to know the social structure of local community, and social capital in social structure of Akit community so they can overcome Life issues. This research was conducted in Berancah Village of Bantan District of Bengkalis Regency, with the largest population of Akit in Bantan District, Bengkalis Regency. This research is a Quantitative research with simple statistical technique. This type of research is descriptive in the form of studies conducted on the location and certain characteristics found in the field for the reconstruction or getring the right substantive pattern in accordance with the theory used in this study of social capital.